THE RELEVANCE AND IMPACT OF SOUTH AFRICAN LABOUR LAW IN THE MINING SECTOR: A FOURTH INDUSTRIAL REVOLUTION PERSPECTIVE - Faheemah Karolia-Hussain; Elmarie Fourie (Obiter, 2021)
The mining sector is one of the contributors to the South African economy and improving productivity is important if it is to remain competitive in the global marketplace. Thus, the technologies that will be created by the Fourth Industrial Revolution (4IR) are important to the mining sector. However, if this leads to mining companies being less reliant on labour, then these changes will have a negative impact on the jobs of mineworkers.This article looks at the legal framework that governs the mining sector in South Africa in the context of 4IR. The Labour Relations Act (LRA) provides for collective bargaining and strike action, but collective bargaining in the South African mining sector is failing and has not produced the desired result. Strike action has become more common and strikes are often violent and unprotected. Secondly, occupational health and safety risks are present in the mines despite protective legislation – namely, the Mine Health and Safety Act (MHSA). Workers experience harsh working conditions underground. Lastly, workers’ skills need to be developed if they are to retain their jobs in 4IR. In terms of legislation, workers should receive training if such training is available for their sector. Consideration urgently needs to be given to the impact on and relevance of 4IR to the labour legal framework in the mining sector. Furthermore, changes to the law in readiness for 4IR and its impact on the workforce in the mines should be considered.